SAT0001 Identification of Sjögren's Syndrome Risk Loci near TNFAIP3 and PRDM1. (15th July 2016) - Lessard, C.; Li, H.; Ice, J.A.; Adrianto, I.; Rasmussen, A.; Lewis, D.M.; Radfar, L.; Stone, D.U.; Montgomery, C.G.; Rhodus, N.L.; Scofield, R.H.; Farris, A.D.; et al.
Abstract : Background: Sjögren's syndrome (SS) is a complex autoimmune disease with both environmental and genetic factors playing important roles in its etiology. Objectives: The goal of this study was to replicate 8 suggestive loci that failed to exceed the genome-wide significance (GWS) threshold of 5x10E-8 in our previously published work: TNFAIP3, PTTG1, PRDM1, DGKQ, FCGR2A, IRAK1BP1, ITSN2, and PHIP . Methods: Our previous study included 1638 SS cases and 6754 population controls. In the current study, we genotyped an additional 282 SS cases and 2576 population controls yielding a total of 1920 SS cases and 9330 controls. Analysis was done using logistic regression accounting for ancestry and gender. Results: Two regions exceeded the GWS threshold. Association has been previously established with SS to a risk haplotype spanning the TNFAIP3 coding region described in lupus; however, we identified a novel independent effect ∼230kb 5' of TNFAIP3 (rs6933404 Pmeta =6.85x10E-9, OR=1.28) originally described in rheumatoid arthritis. Association was observed for the haplotype spanning the TNFAIP3 coding region peaking at rs58721818 (P=4.77x10E-4), which is not correlated with rs6933404 ( r 2 =0.02; D'=0.49). Bioinformatics data provided limited support that rs6933404 is the functional variant in this region; however, another variant on this haplotype also surpassing GWS, rs6927172, modifies 8 transcription factor binding sites, and is located within an enhancer element in CD4 + CD25 – IL17 + PMA-Ionomycin stimulated Th17 primary cells by the Epigenetics Road Map Project. A variant in the region of PRDM1 also surpassed the GWS threshold (rs526531 Pmeta =1.70x10E-8, OR=1.25). Two additional variants on this haplotype exceeded GWS, but no clear candidate functional variant has emerged based on bioinformatics data. Of the 6 remaining suggestive regions, PTTG1, DGKQ, and FCGR2A continue trending towards GWS. Conclusions: These data now establish 2 new SS risk loci, TNFAIP3 and PRDM1 . TNFAIP3, which codes for the protein A20, is a negative regulator of NF-kB. PRDM1, which codes for the protein BLIMP1, is a transcription factor that regulates interferon-beta locus and plasma cell differentiation. Additional studies are needed to determine how these association signals function in the human genome and contribute to SS etiology. Disclosure of Interest: None declared